Effects of Cognitive Stress on the Temporal Anticipation of a Timing Motor Task - K. Suppiah, Pathmanathan (2003)
The study was designed to investigate the effects of cognitive stress on the temporal anticipation of a timing motor task. The experimental design applied was a repeated measures design with two independent variables (cognitive stress and levels of difficulty - easy, intermediate and difficult). The participants of this study consist of 18 male and 19 female undergraduates of the Physical Education programme of University Putra Malaysia. The participants were required to perform a timing motor across three levels of difficulty and under two conditions i.e. without cognitive stress and under cognitive stress. Cognitive stress was induced via the continuous subtraction of two from a two-digit number. Participants performed the task individually and the sequence of the experimental task was counterbalanced. A two-way within subject's ANOVA was performed to ascertain the effects of cognitive stress on the temporal anticipation of the timing motor task. The data analysis revealed a significant difference in means for the stress main effect (A = 64, E (1.35) = 19.89, P = .00); and the task main effect (A = .84, E (2,34) = 3.35, p < .05). Post hoc comparisons produced a significant difference in the means of the performance of the timing motor task at all three levels of difficulty. This showed that cognitive stress had an effect on the temporal anticipation of the timing motor task. A two way mixed design ANOVA was conducted was performed to ascertain the effects of cognitive stress on the temporal anticipation of the timing motor task with regard to gender. The task main effect was significant (A = .59, E (5, 170) = 6.70, P = .01). Follow up comparisons revealed significant difference in the performance of the experimental task at the easy level without cognitive stress, intermediate level without cognitive stress and the easy level under cognitive stress. This showed that there was a significant difference in the performance of the timing motor at the three levels mentioned.